2021
DOI: 10.1088/1755-1315/913/1/012089
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hepatoprotector jamu formula (combination of Curcuma longa, Curcuma xanthorrhiza, and Taraxacum officinale) compared to Fructus schizandrae extract in mild liver injury: a randomized controlled trial

Abstract: The prevalence of impaired liver function in developing countries is increasing. Indonesia has several traditional medicines that can be used as alternative treatments for liver dysfunction. The aim of this study was to determine the efficacy of hepatoprotector jamu formula (combination of Curcuma longa, Curcuma xanthorrhiza, and Taraxacum officinale) compared to Fructus schizandrae fruit extract for treating mild liver injury. This study was a RCT using parallel open label design which involved 60 subjects fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This decrease in AST enzyme activity indicates an improvement in the liver provided by the extract. Group 1 given the temulawak extract 35 mg/kg BW had the highest AST enzyme activity with a level of 121,929 U/L which indicated that this dose was still unable to provide a good hepatoprotective effect where the hepatoprotective effect of temulawak according to Ardiyanto et al [27] observed at 100 mg/kg BW.…”
Section: Groupmentioning
confidence: 94%
“…This decrease in AST enzyme activity indicates an improvement in the liver provided by the extract. Group 1 given the temulawak extract 35 mg/kg BW had the highest AST enzyme activity with a level of 121,929 U/L which indicated that this dose was still unable to provide a good hepatoprotective effect where the hepatoprotective effect of temulawak according to Ardiyanto et al [27] observed at 100 mg/kg BW.…”
Section: Groupmentioning
confidence: 94%
“…Out of those, 541 RCTs were eliminated, because they did not report our outcomes of interest. We disqualified 21 RCTs that investigated the effect of curcumin/turmeric in combination with other components, such as anthocyanins, resveratrol, ginger, pepper, and omega-3 fatty acids only in the intervention group(Abdolahi et al, 2018;Ardiyanto et al, 2021;Biagi et al, 2018;Birudaraju et al, 2020;Briata et al, 2021;Chiosi et al, 2022;Cruz-Correa et al, 2006;Derosa et al, 2018;Haroyan et al, 2018;Hatab et al, 2019;Ide et al, 2010;Irving et al, 2015;Lopresti & Drummond, 2017;Ortiz et al, 2019;Ozdatli et al, 2016;Petrera et al, 2015;Rao et al, 2019;Sanatani et al, 2015;Soveyd et al, 2017;Vaughn et al, 2018;Yazdani et al, 2021). Moreover, we excluded four RCTs, because they were conducted on children(Manarin et al, 2019;Nowak et al, 2020Nowak et al, , 2022Talebi et al, 2021).Two additional studies were removed in which the duration of the intervention was less than 2 weeks(Amalraj et al, 2020;Shadnoush et al, 2020).…”
mentioning
confidence: 99%